Executive Committee Minutes 2011-09-22 - Academic Senate:::::::::
Change of name and timeline for Gender and Sexual Health Stakeholder's Exploratory Workgroup, Question from FSAC re: revising (Student Evaluation of Teaching Effectiveness instrument) SETEs, Spring University Retreat